(untitled) (Philadelphia, PA, 2002)
The highly popular Secrets SeriesÂ® presents an important new resource for veterinarians in this comprehensive, yet focused, coverage of one of the most important and fastest-emerging specialties in veterinary medicine. Among the topics covered are Patient Management, Preparation, Pharmacology, Monitoring, Anesthetic Complications, Anesthesia and Systemic Disease, Special Anesthetic Considerations, Regional Anesthesia, and Pain Management for Small Animals.
Keywords: Veterinary anesthesia,Pain in animals,Gây mê thú y,Đau ở động vật; Treatment,Điều trị